PENGARUH PERISTIWA PENGUMUMAN KABINET KERJA JOKOWI DAN JUSUF KALLA TERHADAP PASAR MODAL DI INDONESIA - Wijayanti, Siti Nur; Sulistiyani, Tina (Universitas Ahmad Dahlan, 2014)
The purpose of this research is to analyze the effect of announcement event from Kabinet Jokowi-Jusuf Kalla toward capital market in Indonesia as seen in the stock price differences and occurences of abnormal return. This research uses event study research method conducted for 30 days. That is the first fifteen days before the event the event and fifteen days after the event began from October 6th, 2019 until November 14th, 2014. The testing instrument used for seeking the differences of stock price in every company uses Paired Sample T Test. While for abnormal return testing the researcher uses One Sample T Test. The result of the research shows that announcement effect of Kabinet Kerja Jokowi-Jusuf Kalla in Indonesian capital market gives significant difference on 14 companies from 24 companies which is incorporated in Jakarta Islamic Index (JII) in period of June to November 2014. The second result of the research shows a presence of abnormal return that can be seen on Ciputra Development Tbk. Because of announcement effect from Kabinet Kerja Jokowi-Jusuf Kalla in Indonesian capital market.